Use of artificial intelligence in university education: a systematic review - Tinoco-Plasencia, Christian Jairo (2023)
The emergence of different technological advances has affected all sectors of society, especially education. In this framework, artificial intelligence has stood out in university education. The objective of the study was to explore the research developed and existing scientific information on the use of artificial intelligence in university education. The specific objectives were: to specify the findings achieved in studies on the use of artificial intelligence in university education and to determine the benefits of the use of artificial intelligence in university education. From the methodological field, the study was of a documentary type, bibliographic design, framed in a systematic review. Likewise, the PRISMA diagram was created for sample selection. Articles indexed in the Web of Science database were selected. The search was carried out using the descriptors: artificial intelligence and university education, and the “AND” connector was also used. The inclusion criteria applied were: articles that address artificial intelligence in university education; articles published between 2021 and 2023; articles in any language; original articles and open access articles. Likewise, the exclusion criteria were: systematic review articles, letters and expert opinions. Applying these criteria and following the PRISMA diagram procedure, 10 publications were selected to make up the sample. It is highlighted that to date there are very few studies on the application of artificial intelligence in university education, considering various factors, such as ease of access and the knowledge necessary for its management. However, these studies had positive results in the teaching-learning process of university students.